2007
DOI: 10.1002/tox.20236
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of methylmercury and selenium on the bioaccumulation and histopathology in medaka (Oryzias latipes)

Abstract: Interaction of methylmercury and selenium in medaka (Oryzias latipes) on bioaccumulation of pollutants and histopathological changes in liver and gill were studied. Juvenile medaka fish were submitted to a series of waterborne methylmercury chloride (MMC), sodium selenite (Na 2 SeO 3 ) and their mixture for 210 days, respectively. The methylmercury (MeHg) and selenium contents in the whole body of medaka were determined. The dose-and time-dependent increase of MeHg and selenium contents in medaka were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…However, it seems that a threshold concentration of selenium in fish body parts must be reached before a clear protective role of selenium against mercury assimilation becomes noticeable [150]. Also, concurrent exposure to methylmercury chloride and selenite led to increased selenium accumulation in medaka fish [151]. The influence of mercury on endogenous selenium after lifelong or acute exposure to mercury vapour (Hg 0 ) has also been studied in man and animals [132].…”
Section: Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it seems that a threshold concentration of selenium in fish body parts must be reached before a clear protective role of selenium against mercury assimilation becomes noticeable [150]. Also, concurrent exposure to methylmercury chloride and selenite led to increased selenium accumulation in medaka fish [151]. The influence of mercury on endogenous selenium after lifelong or acute exposure to mercury vapour (Hg 0 ) has also been studied in man and animals [132].…”
Section: Traffickingmentioning
confidence: 99%
“…Later, studies with human malignant melanoma cells demonstrated that arsenite-induced apoptosis is prevented by selenite [32]. A Human cells As-induced apoptosis is prevented by Se [32] A Mice As prevents carcinogenic effect of Se [30] A Rats As prevents carcinogenic effect of Se [31] A Rats As protects against the toxicity of Se (growth, mortality rate, pathological condition of the liver) [20,33,186] A Rats As induces mucosal glutathione synthesis, explaining its protective effect against Se [187] A Dogs As antagonizes Se-induced subnormal growth and restricted food intake [35] A Cattle As protects against Se toxicity [36] A Hogs As protects against Se toxicity [ Se prolongs the half-lives of Hg-exposed animals [190] A Rats Se changes the subcellular Hg distribution [191] S Oysters High levels of Se increase Hg toxicity [192] SeO 3 2− /MeHg + A Chickens Se changes the subcellular and pattern distribution of Hg [193] A Medaka fish Se protects against Hg-induced histopathological changes [151] SeO 2 /Hg 2+ A Chicks Se toxicity is decreased by Hg [194] SeO 4 2− /MeHg + A Mice Se protects against Hg-induced neurotoxicity [63] Protective effects of arsenic in rats [19,20,23,33,34], dogs [35], cattle [36], mice [37], hogs [38], steers [39], mallards [40] and poultry [41][42][43] have been observed/proposed. Several studies apparently suggest that the same interaction can occur in humans [44][45][46]…”
Section: Arsenic and Seleniummentioning
confidence: 99%
“…For example, tributyltin exposure could induce cellular pathological alterations including vacuoles with increasing number and size, swelling of mitochondria, abnormal nuclei and decreases of rough endoplasmic reticulum cisternaes in the liver of the Chinese rare minnow (Gobiocypris rarus) [106]. Histopathological changes, such as oedema, vacuolization, pyknotic nucleus, telangiectasis and degenerative sperm were found in the liver, gill and gonad slices from medaka (Oryzias latipes) exposed to methylmercury [107]. The interaction between mercury and selenium was debated previously [108][109][110][111].…”
Section: Morphological Observation-imposex As a Typical Examplementioning
confidence: 99%
“…The interaction between mercury and selenium was debated previously [108][109][110][111]. The histopathological observations helped to find that the interaction between MeHg and selenium at molar ration of 1:1 offered a limited protection against of both MMC and Na 2 SeO 3 to medaka [112]. Accordingly, histopathological techniques can be obviously used to evaluate the toxicological effects of both individual pollutant and the complex chemicals.…”
Section: Morphological Observation-imposex As a Typical Examplementioning
confidence: 99%
“…Many estuarine and marine species are able to absorb and accumulate metals from water or feed. In context of heavy metal uptake, there are many studies on several fish, oyster and large crustacean species [16][17][18][19][20][21][22][23], but little information is available regarding metal uptake capacity in planktonic crustaceans [24][25][26]. Artemia urmiana is an endemic species of Artemia in Iran [27] and in spite of high economic and ecological importance, there is no information about its toxicological aspects.…”
mentioning
confidence: 99%